Analysis of the unique gait mechanism of locusts focusing on the difference in leg length. (1st September 2020) - Sugimoto, Yasuhiro; Sugiyama, Shuntaro; Naniwa, Keisuke; Osuka, Koichi
Abstract : The various types of gaits shown by insects are very interesting, and many studies have been conducted to investigate the mechanism of these gaits. In nature, there are many insects with apparent differences in the length of each leg, and it seems that the difference in leg length may affect the resultant gait of insects. However, there has not been much discussion about the influence of these differences in leg length on the gait. In this research, in order to investigate the influence of the difference in leg length on gait, we focus on locusts, whose hind legs are considerably longer than the other legs and shows a unique gait not seen in other insects. First, we measure the kinematics of gait of some insects, including locusts, and analyze the unique gait specific to locusts. Next, we reproduce this unique gait via numerical dynamical simulation. By conducting some simulations while changing the length of the legs, we investigate the mechanism of the unique gait of locusts and the influence of difference in leg length on walking. As a result, it is confirmed that the unique gait of locusts can be reproduced with a combination of long hind legs (compared to the front and middle legs) and the adjustment of the stroke and period of the hind leg based on horizontal ground reaction force. GRAPHICAL ABSTRACT: UF0001